Answer:
![Sin(Cos^(-1) (14x))=√(1-196x^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ygcmytlhzfwbvahoc0shnlzp8bqb6svt1p.png)
Step-by-step explandation:
First of all, from the figure we can define the cosine and sine functions as
![Cos(theta)=(adjacent )/(hypotenuse )](https://img.qammunity.org/2021/formulas/mathematics/high-school/wz0vlocnnshr0t5coe7ly46fi3vsmcrzj2.png)
![Sin(theta)=(Opposite)/(hypotenuse )](https://img.qammunity.org/2021/formulas/mathematics/high-school/zknu36tyw1m6f8t96tgs1cxp0hq41tr6k3.png)
And by analogy with the statement:
![14x=(adjacent )/(hypotenuse )](https://img.qammunity.org/2021/formulas/mathematics/high-school/jywwbxknex98vsg6o6gnqk1u9egww2vff9.png)
Which can be rewritten as:
![(14x)/(1)=(adjacent )/(hypotenuse )](https://img.qammunity.org/2021/formulas/mathematics/high-school/vlcu1n05cv9fkbashky4yb3gk2x5gmx8ei.png)
You have then that, for the given triangle, the values of the adjacent and hypotenuse sides, are then given by:
:
Adjacent=14x
Hypotenuse=1
And according to the Pythagorean theorem:
![Opposite=√(1-(14x)^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7tucyhfszxi1ckbyrmzp63o9i7dh4m6kh3.png)
Finally, by doing:
![Cos^-1(14x)=theta](https://img.qammunity.org/2021/formulas/mathematics/high-school/oh2kzsxnzqfondlm28bywk4kcpij8cypd0.png)
We have that:
![Sin(Cos^(-1) (14x))=Sen(theta)=(Opposite)/(hypotenuse)=(√(1-(14x)^2))/(1)=√(1-(14x)^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5nbskh6xjiew3i7eeh00r9ky59w4jyo6sq.png)